2021
DOI: 10.3389/fcvm.2021.691336
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Purification Treatment Relieves the Damage of Hyperlipidemia to PBMCs

Abstract: Background: Hyperlipidemia {hypercholesterolemia [cholesterol >5.18 mmol/L) or hypertriglyceridemia [triglycerides >2.3 mmol/L], mixed hyperlipidemia [cholesterol >5.18 mmol/L and triglycerides >2.3 mmol/L], and high low-density lipoproteinemia [low-density lipoprotein (LDL) >3.4 mmol/L]} is a strong risk factor for arteriosclerosis and cardiovascular disease (CVD). Therapy with lipid-lowering drugs often results in many side effects. Our study aimed to investigate the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Then, the corresponding secondary antibodies were incubated according to the source of primary antibodies, which were mouse and rabbit antibodies, respectively. Finally, the results were quantified by ImageJ software (Scion Corp., USA) [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Then, the corresponding secondary antibodies were incubated according to the source of primary antibodies, which were mouse and rabbit antibodies, respectively. Finally, the results were quantified by ImageJ software (Scion Corp., USA) [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Beside non-statin therapies, other therapeutic options have emerged to meet the need for reducing circulating LDL-C. Double-filtration plasmapheresis (DFPP) is a lowcost treatment used to decrease LDL-C concentrations in patients with dyslipidaemias, such as homozygous familial hypercholesterolemia (HoFH) (10). In their original publication, Zhang et al sought to investigate the potential effects of nondrug therapy with double-filtration plasmapheresis (DFPP) on lipid metabolism-, endoplasmic reticulum (ER) stress-, and apoptosis-related proteins in peripheral blood mononuclear cells (PBMCs) before and after lipid clearance in patients with hyperlipidemia (11). In line with a previous study that reported that lipid plasmapheresis reduced plasma PCSK9 levels (12), they show that DFPP induces the downregulation of PCSK9, CD36 and LDLR in PBMCs.…”
mentioning
confidence: 99%